Exosomes Derived from SW480-Resistant Colon Cancer Cells Are Promote Angiogenesis via BMP-2/Smad5 Signaling Pathway - Song Yang; Lei Yao; Xiaolong Wang; Hao Sun; Chaogang Du; Chengpeng Song; Jingyu Fu; Yongjun Wu; Hongwu Huang; Chuansi Wang; Yongsen Wang; Yixiang Xie (Applied Bionics and Biomechanics)
Background. Multidrug resistance is the main cause of tumor recurrence and metastasis. Therefore, it is urgent to explore the mechanism and treatment of drug resistance of tumor cells. We aim to investigate the relationship between drug resistance and angiogenesis in SW480 colon cancer cells and the possible underlying mechanism. Methods. Exosomes were extracted from SW480-sensitive or SW480-resistant colon cancer cells (SW480/oxaliplatin). The CCK-8 assay, migration assay, tube formation assay, qPCR, and Western blotting were performed in human umbilical vein endothelial cells (HUVECs). The underlying mechanisms were detected by Western blotting assays and BMP-2 si-RNA silencing assay in vitro and in vivo. Results. The conditioned medium and exosomes of SW480/oxaliplatin cells promoted proliferation, migration, and tube formation of HUVECs. The expression of BMP-2 released by SW480/oxaliplatin exosomes was 2.3-folds higher than that by SW480 exosomes. Additionally, exosomal BMP-2 inhibiting the Smad signaling pathway induced the expression of vascular endothelial growth factor and CD31. Silencing of BMP-2 partly blocks the promoting effect of SW480/oxaliplatin exosomes on angiogenesis. Moreover, SW480/oxaliplatin cells increased the BMP-2 expression, consequently promoting angiogenesis in vivo. Conclusions. SW480-resistant colon cancer exosomes promoted angiogenesis via the BMP-2/Smad signaling pathway, which is potential for the novel treatment for antiangiogenic therapies in colon cancer.